Antifungal properties of peptidomimetics with an arginine-[β-(2, 5, 7-tri-tert-butylindol-3-yl)alanine]-arginine motif against Saccharomyces cerevisiae and Zygosaccharomyces bailii. Issue 3 (10th March 2015) - Larsen, Camilla Eggert; Larsen, Camilla Josephine; Franzyk, Henrik; Regenberg, Birgitte
Abstract : Due to increased occurrence of infections and food spoilage caused by yeast, there is an unmet need for new antifungal agents. The arginine-β-(2, 5, 7-tri- tert -butylindol-3-yl) alanine-arginine (R-Tbt-R) motif was previously proved useful in the design of an antifungal tripeptide. Here, an array of peptidomimetics based on this motif was investigated for antifungal and hemolytic activity. The five most promising modified tetrapeptide analogues (6 and 9–12) contain an additional C-terminal hydrophobic residue, and these were found to exhibit antifungal activity against Saccharomyces cerevisiae (MIC 6 and 12 μg mL −1 ) and Zygosaccharomyces bailii (MIC 6–25 μg mL −1 ). Four compounds (6 and 9–11), had limited hemolytic activity (<10% hemolysis at 8 × MIC). Determination of their killing kinetics revealed that compound 9 displayed fungicidal effect. Testing against cells from an S. cerevisiae deletion mutant library indicated that interaction with yeast-specific fungal sphingolipids, most likely constitutes a crucial step in the mode of action. Interestingly, a lack of activity of peptidomimetics 6 and 9–11 towards Candida spp. was shown to be due to degradation or sequestering by the yeast. Due to their ultrashort nature, antifungal activity and low toxicity, the four compounds may have potential as leads for novel preservatives. Abstract : Peptidomimetics based on the Arg-Trp-Arg motif are antifungal agents. Abstract :